Evaluate the Effectiveness of Bone Grafts by two Techniques (Wedge Technique) in the three-dimensional Alveolar Augmentation of Atrophic Bone: Clinical and Radiological Study - يعقوب حكمت; الخطيب هيا (Latakia University Journal -Medical Sciences Series, 2020)
The aim of this study is to evaluate the efficiency of the wedge technique, in which the study sample consisted of eight patients whose ages ranged between 18 to 40 years suffering from bone loss resulting from the surgical removal of cysts and tumors or from the bone absorption following dental extraction. The bone graft was harvested from the chin area as a full thickness bone block and then the block was adapted by separating the concellouse bone from it and then splitting the cortical bone so we can form bone wedges from it and then place them in the bone grooves within the recipient area and filling the spaces between the bone wedges by concellouse bone grafts. Patients were followed up after two and six months. Results: The results of the study showed a clear increase in the dimensions of bone grafting in the wedge method before vaccination and after two and six months, while it did not change much between two and six months. The study results also showed that the average density in the wedge method decreased after six months from two months later where it was the decrease was significant. Conclusions: The results of this study showed the effectiveness of this technique in securing a three-dimensional increase in areas of major bone loss.